Classification of Quranic Verses On The Learning of Mathematics - Rora Rizky Wandini; Syamsu Nahar; Rusydi Ananda (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research aims to conduct an analysis and identification of Quranic verses related to the teaching of mathematics in the Teacher Education Program for Madrasah Ibtidaiyah (PGMI) State Islamic University of North Sumatra (UIN SU) in Medan. The objective is to develop a Quranic verse classification application on mathematics learning and assess the feasibility, effectiveness, and practicality of the produced product. The research employs the Research and Development (R&D) 4D Thiagarajan method, which includes the stages of defining, designing, developing, and disseminating. The Result 1) The understanding level of PGMI students showed improvement from the pre-test results. The experimental class increased from 55.84 in the pre-test to 85.12, while the control class increased from 67.82 to 70.52. 2) The design and development of the product began with the identification of measurable objectives for application creation, recognition of the target audience, design of features within the application, and selection of the technological platform supported by the application. 3) The product produced in this research is deemed highly feasible and practical after undergoing validity tests conducted twice. Content validity, assessed by experts, received scores of 3.35 for material (categorized as highly feasible) and 3.37 for design (categorized as highly feasible). Construct validity, with an alpha of 0.4330 (categorized as practical), and a t-test for the difference in results between the experimental group after (85.12) and the control group after (70.52) showed a confidence interval of 95% for the average difference as [-20.50, -8.69].